The Impact of Quality of Work Life and Work-Life Balance on Job Satisfaction: The Mediating Role of Perceived Organizational Support - Glend Felix Siagian; Chairul Muriman Setyabudi; Vita Mayastinasari (Borong Newinera Publisher, 2024)
Human resources are a crucial factor in achieving organizational success. Therefore, job satisfaction plays a significant role in the success of an organization. This study collected data from 290 members of the Tulang Bawang Police through questionnaires distributed between September and December. The analysis utilized structural equation modeling (SEM). The study found that both quality of work life and work-life balance had a positive and significant impact on job satisfaction. Additionally, quality of work life and work-life balance had a positive and significant effect on perceived organizational support. Furthermore, perceived organizational support mediated the relationship between quality of work life and work-life balance and job satisfaction. Finally, the study found that perceived organizational support had a positive and significant effect on job satisfact.